3r concept (reduce, reuse, recycle) among form six students in Kudat - Norsahirah binti Maulana; Mohammad Tahir Bin Mapa; Pricilla Tan (Fakulti Kemanusiaan, Seni dan Warisan, UMS, 2023)
The 3R concept (reduce, reuse & recycle) was introduced at the school to practice recycling thereby reducing waste generation at the source. However, awareness of the importance of this concept is still unsatisfactory among students. This study was conducted to identify the student’s engagement and knowledge of the 3R concept and suggestions to increase student awareness at school. The survey involves a total of 100 students as respondents which is each school represents 50 students from SMK Kudat and SMK Abdul Rahim. The data obtained were analyzed by SPSS software (Statistical Package for Social Science) using descriptive analysis to obtain percentage and frequency as well as correlation analysis to assess the relationship between knowledge and student engagement in the 3R activities. The results found that each school has an alternative to implement the 3R concept. Student knowledge is mostly satisfactory. There is the relationship between the variables that are higher knowledge among students directly increases the level of involvement in 3R activities at school. The lack of 3R disposal bins has made students use an ordinary bin. Suggestion for the addition of 3R bins and the implementation of 3R activities among students.